2019
DOI: 10.12659/ajcr.915600
|View full text |Cite
|
Sign up to set email alerts
|

Choledochoduodenal Fistula Secondary to Peptic Ulcer Disease: A Case Report

Abstract: Patient: Female, 29 Final Diagnosis: Choledocho-duodenal fistula Symptoms: Abdominal pain • nausea • vomiting Medication: — Clinical Procedure: Gastro-jejunostomy • hepatico-jejunostomy Specialty: Surgery Objective: Rare co-existance of disease or pathology Background: Choledochoduodenal fistula is an uncommon complication secondary to peptic ulcer disease. Determining this dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Several therapies have been proposed to treat entero-biliary fistula but no guidelines have been established yet ( 6 , 8 ). It is recommended to treat cholecysto-duodenal fistula surgically with cholecystectomy and closure of the fistula tract ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several therapies have been proposed to treat entero-biliary fistula but no guidelines have been established yet ( 6 , 8 ). It is recommended to treat cholecysto-duodenal fistula surgically with cholecystectomy and closure of the fistula tract ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to several authors, a surgical approach should be advised in case of failed medical treatment, gastric outlet obstruction, haemorrhage, perforation, recurrent gallstone ileus or recurrent cholangitis ( 5 , 8 , 32 , 43 ). For CDF due to PUD refractory to medical treatment, a vagotomy with an antrectomy and a reconstruction according to Billroth II procedure with a gastrojejunostomy can be performed ( 7 , 32 , 33 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical structure of the common bile duct features two physiological strictures: one occurs at the junction where the common bile duct enters the duodenum, and the other is at the duodenal papilla. Repeated stimulation of oppression and chronic inflammatory reactions, or long-term oppression of adjacent organ tumors, can cause damage to the bile duct wall, forming a fistula [1] . Another study reported that the common cause of CDF is duodenal ulcer, and the inflammatory reaction of larger ulcers is more severe, causing it to penetrate the duodenal wall and form a fistula with the rear common bile duct [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Enteroenteric fistulae often secondary to benign or malignant disease, such as colon cancer ( 1 ), Crohn's disease ( 2 ), radiation enteritis ( 3 ), peptic ulcer disease ( 4 , 5 ), and acute bowel ischemia ( 6 ), but duodenal fistulae are relatively rare. Additionally, among duodenal fistulae, internal duodenocolic fistulaes are relatively common, but duodeno-ileum fistulaes are rare.…”
Section: Discussionmentioning
confidence: 99%